Outcome differences in HPV-driven head and neck squamous cell carcinoma attributable to altered human leukocyte antigen frequencies - Wichmann, Gunnar; Vetter, Nathalie; Lehmann, Claudia; Landgraf, Ramona; Doxiadis, Ilias; Großmann, Rebecca; Vorobeva, Ekaterina; Dietz, Andreas; Zebralla, Veit; Wiegand, Susanne; Wald, Theresa (Frontiers in Oncology, 2023)
Background: Effective immune surveillance requires a functioning immune system and natural killer (NK) and T cells for adequate innate and antigen-specific immune responses critically depending on human leukocyte antigens (HLA) and haplotypes representing advantageous combinations of HLA antigens. Recently we reported a link between altered frequencies of HLA alleles and haplotypes and developing head and neck squamous cell carcinoma (HNSCC). Whereas the majority of HNSCC seems to be related to classical risk factors alcohol and tobacco, a subset of HNSCC and especially oropharyngeal squamous cell carcinoma (OPSCC) were etiologically linked to human papillomavirus (HPV) recently. Here we demonstrate in HPV-driven (p16-positive high risk-HPV DNA-positive) HNSCC a deviating distribution of HLA antigens and haplotypes and their relevance for outcome. Methods: Leukocyte DNA of n=94 HPV-driven HNSCC patients (n=57 OPSCC, n=37 outside oropharynx) underwent HLA SSO typing allowing allele, antigen (allele group) and haplo-typing. Besides comparing these frequencies with those of German blood donors, we analyzed their impact on outcome using Kaplan-Meier plots and Cox proportional hazard regression. Results: Antigen and haplotype frequencies demonstrate enrichment of rare antigens and haplotypes. The HLA score for unselected HNSCC patients was not predictive for outcome here. However, together with alcohol consumption, tobacco smoking, T category and extranodal extension of locoregional metastases and treatment applied, 8 HLA traits allow for predicting progression-free and tumor-specific survival. Conclusion: Patients can be categorized into low, intermediate-low, intermediate-high and high-risk groups. Using a new PFS-risk score for HPV-driven HNSCC may allow to improve prognostication.